Intrinsic noise within viscous solids and impact on material exploration - Fa, Lin; Meng, Shuangshuang; Yang, Huiting; Li, Jinyue; Hu, Yaming; Zhang, Kaiqiang; Xu, Yulin; Zhao, Meishan (Frontiers in Physics, 2025)
This paper introduces the concept of the intrinsic-noise-atom (i.e., intrinsic-noise-element) and its applications. We propose a method to extract intrinsic noise generated within viscous solids and discuss its impact on material exploration and analysis. The analysis is designed to improve our ability to explore viscous material, enhancing the inversion of physical formation characteristics in acoustic logging while drilling. We show that under a harmonic single-frequency force, the medium viscosity and the particles’ inertia inside the viscous solids lead to a transient process from the static state to the stable state of a harmonic single-frequency vibration. The spectrum corresponding to this transient process reveals information on the intrinsic noise within viscous solids. A damped oscillatory spring model of particle vibration corresponding to longitudinal wave propagation is established, and the acoustic impulse response and system function are obtained, where we can extract the intrinsic noise signal from the vibration state generated by the particle under the action of harmonic single-frequency force. Based on a representative frequency spectrum, the characteristics of the physical formation around the drilled oil well can be retrieved to determine whether it is a hydrocarbon reservoir and if there are deformations, such as fractures, or if it is in good condition. With its reliability, this method can effectively extract the intrinsic noise and successfully retrieve the characteristics of the physical formation of solid media.